Navigating the Knowledge Network of New Venture and Small Business: Bibliometric Insights and Forward-Looking Perspectives - Idzani Muttaqin; Budi Setiadi; Noorlaily Maulida; Ayu Niken Faizati; Rizka Zulfikar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The purpose of this research was to navigate the intricate knowledge network that underpins new ventures and small businesses through bibliometric analysis. The primary data source using the Scopus database, 123 peer-reviewed documents including journal articles, conference papers, and book chapters which published in period 2003-2025 were systematically selected following the PRISMA framework to ensure transparency and eliminate bias. The research applies the Biblioshiny interface for R to conduct multidimensional analyses covering source impact, document influence, keyword trends, and conceptual structures. The findings reveal an increasingly dynamic knowledge network characterized by the dominance of themes such as entrepreneurship, innovation, small firm strategy, and internationalization. The co-occurrence network uncovers interrelated conceptual clusters, while the thematic evolution map traces a shift from foundational entrepreneurship themes to more contemporary concerns like digital transformation and ecosystem resilience. Highly cited papers were clustered in influential journals such as Small Business Economics and the International Journal of Entrepreneurial Behaviour and Research, underscoring the interdisciplinary depth of the field. The study offers both theoretical and practical implications. For academics, it identifies underexplored yet promising areas such as absorptive capacity and entrepreneurial ecosystems, while practitioners may leverage insights to strengthen knowledge-sharing strategies and innovation capacity.